The visual image in the high school history textbook of the Paraíba state system investigated from the perspective of Archaeological Discourse Analysis - Eduardo Jorges Pugliesi (Universidade Estadual de Alagoas, 2021)
The 21st century has as its indelible mark the ubiquity of the visual image in its various genres, so it is necessary to develop approaches tht allow to approach it in its field of existence. The school as a cultural space has as its purpose the training of social subjects and in this way, it plays a very important role. For, it performs the mediating function throug the educationalpractices of accumulated historical knowledge that are present in the textbooks used in it. It is from this place that this research offers itself to investigate the order of discourse in the high school history textbooks of the state network of Paraíba established by the enunciative series that position the visual images along them. The theoretical-methodological approach chosen to carry out the analysis of the findings was the Archeological Theory of Discourse (TAD), by Michel Foucault (2015) wich has anoperating horizon based on three stages, namely: map, excavate and analyze descriptively (ALCANTARA; CARLOS, 2013) wich operates as follows: in the firt stage -the horizontalization phase of the research, represents the moment in which we collected the data, the information,where the first evidence is found; in the second stage -the phase in which the research will be verticalized, marks the instant when we look at what was selected and thus constitute the archeological terrain of the investigation, theplace where the excavation will take place by choosing the most appropriate tools; in the third and last stage -occasion when the findings of the research will be communicated.